PELAKSANAAN DIDIK HIBUR DALAM PENGAJARAN DAN PEMBELAJARAN MEMBACA BAHASA MELAYU MURID LINUS TAHUN 3 = Implementation of Fun Learning in Teaching and Learning for Reading Bahasa Melayu of the Year 3 Linus Students - Pauline, Unjong; Zuraini, Seruji (Universiti Sultan Zainal Abidin, Malaysia, 2022)
This study is to obtain information about the fun learning techniques in education for the Malay language that focuses on teaching and learning specifically for LINUS Year 3 students used by teachers from three schools selected in the Sibu district for the study sample. This study was conducted to identify the use of fun learning techniques involving four essential elements which are singing, storytelling, acting, and using pantun. The implementation of this study to carry out quantitative analysis by applying investigative instruments. The instruments of the investigation are to answer by the teachers involved in this study. The study showed that using the teaching method using these four elements can improve the reading skills of LINUS Year 3 students, and teachers use fun learning techniques in teaching and reading the Malay language for LINUS Year 3 students. The implementation of fun learning in teaching Malay language using singing techniques shows that the overall mean is at a high level (M = 4.02, SP = 0.71), storytelling technique (M = 3.87, SP = 0.60), acting technique (M = 3.74, SP = 0.58) and pantun technique indicate the overall mean is at a simple stage (M = 3.50, SP = 0.74). In conclusion, using fun learning techniques to entertain using the four important elements can improve Malay language reading skills and positively impact the learning process of LINUS Year 3 students.